Hot-pressed member and hot-pressed steel sheet and method for manufacturing the same

CN116348215BActive Publication Date: 2026-10-30JFE STEEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180070291.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2021-08-18
Publication Date
2026-10-30
Estimated Expiration
2041-08-18

AI Technical Summary

Technical Problem

但是,大多数情况下,伴随着钢板的高强度化,其冲压成形性降低,因此,难以得到复杂的部件形状

Benefits of technology

[0032]根据本发明,能够得到涂装后耐腐蚀性、特别是应用锆系化学转化处理的情况下的涂装后耐腐蚀性和释氢特性优良的热压构件。另外,根据本发明,能够得到适合于涂装后耐腐蚀性和释氢特性优良的热压构件的热压用钢板。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116348215B_ABST
    Figure CN116348215B_ABST
Patent Text Reader

Abstract

The present application provides a hot-pressed member, a steel sheet for hot pressing, and a method for manufacturing the same. The hot-pressed member of the present application has a Zn-based alloy plating layer on at least one surface of a steel sheet, the Zn-based alloy plating layer having a solid solution phase containing Zn and the balance of Fe and inevitable impurities, an intermetallic compound phase containing Fe and the balance of Zn and inevitable impurities, and an oxide layer containing Zn, the oxide layer being located at the outermost layer of the Zn-based alloy plating layer, and the oxide layer dividing the intermetallic compound phase, the division density of the oxide layer being 10 or more division sites per mm in at least one cross section.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hot-pressed components and steel sheets for hot pressing, as well as methods for manufacturing the same. In particular, it relates to hot-pressed components and steel sheets for hot pressing that exhibit excellent corrosion resistance and hydrogen release characteristics after coating, as well as methods for manufacturing the same. Background Technology

[0002] In recent years, the automotive industry has seen increased use of high-performance, lightweight steel sheets, particularly high-strength hot-dip galvanized or electro-galvanized steel sheets with rust resistance. However, in most cases, the increased strength of the steel sheets has reduced their stamping formability, making it difficult to obtain complex part shapes. For example, in automotive applications, components requiring rust resistance and difficult to form include chassis and other running gear, as well as structural components such as B-pillars.

[0003] Against this backdrop, in recent years, the manufacturing of automotive parts using hot pressing, which is easier to balance stamping formability and high strength than cold pressing, has increased rapidly, leading to the development of various technologies to address the challenges of hot pressing technology.

[0004] In particular, when using Zn-based alloy coated steel sheets as hot-pressing steel sheets, the corrosion resistance of the hot-pressed components, which are the final products, can be improved. Therefore, technologies related to hot-pressing steel sheets with zinc-based alloy coatings (Zn-based alloy coatings) have been proposed. For example, Patent Document 1 discloses a hot-pressing steel sheet with a zinc or zinc-based alloy coating on its surface, having a barrier layer on the surface to prevent the evaporation of zinc during heating.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-73774 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] However, in recent years, zirconium-based chemical conversion treatment has become more popular, replacing the previous zinc phosphate-based chemical conversion treatment. There are also requirements for the corrosion resistance of components that are electrodeposited after undergoing this zirconium-based chemical conversion treatment.

[0010] The hot-pressed component disclosed in Patent Document 1 is a hot-pressed component manufactured by heating a Zn-based alloy coated steel sheet. It exhibits excellent corrosion resistance without coating and excellent corrosion resistance after coating with zinc phosphate chemical conversion treatment. However, for the hot-pressed component in Patent Document 1, there is a problem that the corrosion resistance after coating with zirconium-based chemical conversion treatment is insufficient.

[0011] On the other hand, in order to avoid delayed fracture of hot-pressed components, it is desirable to efficiently release the hydrogen that has penetrated into the steel sheet during the manufacturing process of the hot-pressed component. That is, the development of hot-pressed components with excellent hydrogen release characteristics and their manufacturing methods, as well as hot-pressed steel sheets for obtaining hot-pressed components with excellent hydrogen release characteristics and their manufacturing methods, has become a research topic.

[0012] This invention was made in view of the above-mentioned problems, and its object is to provide a hot-pressed component with excellent corrosion resistance after coating, especially with the application of zirconium-based chemical conversion treatment, and a method for manufacturing the same. Furthermore, this invention aims to provide a hot-pressed steel sheet suitable for hot-pressed components with excellent corrosion resistance and hydrogen release characteristics after coating, and a method for manufacturing the same.

[0013] Methods for solving problems

[0014] In order to achieve the above-mentioned problem, the inventors conducted in-depth research and obtained the following insights.

[0015] (1) In order to improve the corrosion resistance and hydrogen release characteristics of the hot-pressed component after coating, the oxide layer is formed in a manner that places the oxide layer at the outermost layer of the Zn-based alloy coating on the surface of the hot-pressed component and divides the intermetallic compound phase. In addition, it is effective to set the division density of the intermetallic compound phase per unit cross section to a specified value or above for the oxide layer.

[0016] (2) By hot pressing a steel plate with a Zn alloy coating having a crack density of more than a specified value per unit cross section, a hot-pressed component with excellent corrosion resistance and hydrogen release characteristics after coating can be obtained.

[0017] (3) As a method for forming cracks with a crack density of a specified value or higher per unit cross section in the Zn-based alloy coating of a hot-pressed steel sheet used in hot-pressed components, the method of immersing the steel sheet with the Zn-based alloy coating in an acidic aqueous solution is effective. Alternatively, the method of imparting strain to the Zn-based alloy coating of the steel sheet is effective.

[0018] Based on the above insights, the main points of this invention are as follows.

[0019] [1] A hot-pressed component having a Zn-based alloy coating on at least one surface of a steel plate, the Zn-based alloy coating comprising: a solid solution phase containing Zn with the balance being Fe and unavoidable impurities, or a solid solution phase containing Zn and containing at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, B with the balance being Fe and unavoidable impurities; an intermetallic compound phase containing Fe with the balance being Zn and unavoidable impurities, or an intermetallic compound phase containing Fe and containing at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, B with the balance being Zn and unavoidable impurities; and an oxide layer containing Zn.

[0020] The oxide layer is located on the outermost layer of the Zn-based alloy coating, and the oxide layer separates the intermetallic compound phase.

[0021] The segmentation density of each unit section in at least one cross section of the aforementioned oxide layer is more than 10 segmentation sites / mm.

[0022] [2] According to the hot-pressed component described in [1], in the two orthogonal cross sections of the oxide layer, the segmentation density of each unit cross section is more than 10 segmentation parts / mm.

[0023] [3] A hot-pressing steel plate, wherein at least one surface of the steel plate contains at least one of Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with a total content of 0.1 to 60% by mass, the balance being Zn and unavoidable impurities, and the amount of the adhering material being 10 to 90 g / m. 2 Zn-based alloy coating,

[0024] The aforementioned Zn-based alloy coating contains cracks that divide the coating.

[0025] The crack density per unit cross section in at least one cross section of the aforementioned Zn-based alloy coating is more than 10 segments / mm.

[0026] [4] According to the hot-pressing steel plate described in [3], in the two orthogonal sections of the above-mentioned Zn alloy coating, the crack density per unit section is more than 10 segments / mm.

[0027] [5] A method for manufacturing a hot-pressed steel sheet, wherein at least one surface of the steel sheet is provided with an amount of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, comprising a total of 0.1 to 60% by mass, the balance being Zn and unavoidable impurities, and the amount of the adhering material being 10 to 90 g / m².2 The steel sheet with the Zn-based alloy coating is immersed in an acidic aqueous solution with a pH below 4.0 for more than 1.5 seconds, or strain is applied to the Zn-based alloy coating.

[0028] [6] In the method for manufacturing hot-pressed steel plates according to [5], the above-mentioned acidic aqueous solution is the plating solution for forming the above-mentioned Zn-based alloy coating.

[0029] [7] A method for manufacturing a hot-pressed component, wherein a hot-pressed steel plate obtained by the manufacturing method described in [5] or [6] is heated to a temperature range of Ac3 phase transformation point ~ 1000°C and then hot-pressed.

[0030] [8] A method for manufacturing a hot-pressed component, wherein a steel plate is heated to a temperature range of Ac3 phase transformation point to 1000°C and then hot-pressed, wherein the steel plate has at least one component on at least one surface containing a total of 0.1 to 60% by mass of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhesion amount of 10 to 90 g / m. 2 The Zn-based alloy coating has cracks that divide the Zn-based alloy coating inside, and the crack density per unit cross section in at least one cross section of the Zn-based alloy coating is more than 10 divisions / mm.

[0031] Invention Effects

[0032] According to the present invention, it is possible to obtain hot-pressed components with excellent corrosion resistance after coating, particularly when subjected to zirconium-based chemical conversion treatment, and with excellent hydrogen release characteristics. Furthermore, according to the present invention, it is possible to obtain hot-pressed steel sheets suitable for hot-pressed components with excellent corrosion resistance and hydrogen release characteristics after coating. Attached Figure Description

[0033] Figure 1 This is a schematic diagram showing a cross-section of a Zn-based alloy coating before hot pressing (before heating), without the formation of cracks.

[0034] Figure 2 This is a schematic diagram showing a cross-section of a Zn-based alloy coating after hot pressing (after heating), without the formation of cracks.

[0035] Figure 3 This is a schematic diagram showing a cross-section of a Zn-based alloy coating before hot pressing (before heating) in the case of cracks forming in the Zn-based alloy coating.

[0036] Figure 4This is a schematic diagram showing a cross-section of a Zn-based alloy coating after hot pressing (after heating) with cracks formed in it. Detailed Implementation

[0037] The embodiments of the present invention will now be described. It should be noted that the following description illustrates a preferred embodiment of the present invention and is not intended to limit the scope of the invention in any way. Furthermore, the unit for the content of each element in the steel composition is "mass%"; unless otherwise specified, it will be expressed in "%".

[0038] 1) Hot-pressed components

[0039] The hot-pressed component of the present invention has a Zn-based alloy coating having a solid solution phase and an intermetallic compound phase on at least one surface of a steel plate. The solid solution phase contains Zn with the balance being Fe and unavoidable impurities, or contains Zn and at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance being Fe and unavoidable impurities. The intermetallic compound phase contains Fe with the balance being Zn and unavoidable impurities, or contains Fe and at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance being Zn and unavoidable impurities. The Zn-based alloy coating has a Zn-containing oxide layer located at the outermost layer of the Zn-based alloy coating. Simultaneously, the oxide layer segments the intermetallic compound phase, and the segmentation density per unit cross-section in at least one cross-section of the oxide layer is 10 segments / mm or more.

[0040] When a steel sheet with a Zn-based alloy coating is hot-pressed, Zn in the coating diffuses into the base steel sheet, forming a solid solution phase containing Zn with the balance consisting of Fe and unavoidable impurities in the diffusion region. Simultaneously, Zn in the coating combines with oxygen present in the heating atmosphere to form a Zn-containing oxide layer. Furthermore, the Zn-based alloy coating, which is an intermetallic compound that does not contribute to either diffusion into the base steel sheet or the formation of the oxide layer, persists directly as an intermetallic compound phase. However, due to the intrusion of Fe diffused from the base steel sheet, it becomes an intermetallic compound phase containing Fe with the balance consisting of Zn and unavoidable impurities.

[0041] On the other hand, when the Zn-based alloy coating contains Zn and at least one element selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, the changes when a steel sheet with this Zn-based alloy coating is hot-pressed are as follows: Zn and other elements in the Zn-based alloy coating diffuse into the base steel sheet, forming a solid solution phase in the diffusion region containing Zn and at least one element selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance being Fe and unavoidable impurities. Simultaneously, the Zn in the Zn-based alloy coating combines with oxygen present in the heating atmosphere to form a Zn-containing oxide layer. Furthermore, the Zn-based alloy coating, which is an intermetallic compound that does not contribute to the diffusion of the substrate steel plate or the formation of the oxide layer, exists directly as an intermetallic compound phase. However, due to the entry of Fe diffused from the substrate steel plate, it becomes an intermetallic compound phase containing Fe and at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities.

[0042] It should be noted that both the solid solution phase and the intermetallic compound phase contain Zn, which has a sacrificial corrosion-resistant effect, thus contributing to improved corrosion resistance. On the other hand, the Zn-containing oxide layer ensures that the zinc phosphate-based chemical conversion treatment and zirconium-based chemical conversion treatment, which are performed as the coating substrate, are uniformly and densely coated, thus contributing to improved coating adhesion. Therefore, to achieve the post-coating corrosion resistance required by this invention, the solid solution phase, the intermetallic compound phase, and the oxide layer are all essential components.

[0043] Furthermore, in this invention, the oxide layer is located on the outermost layer of the Zn-based alloy coating, and it divides the intermetallic compound phase by being located in a direction perpendicular to the surface of the Zn-based alloy coating. The oxide layer only divides the intermetallic compound phase, without dividing the solid solution phase. Additionally, the oxide layer only needs to divide the intermetallic compound phase in at least one cross-section, and is not limited to a specific direction such as a cross-section in the rolling direction or a cross-section perpendicular to the rolling direction. The aforementioned "dividing the intermetallic compound phase" means that the two ends of the oxide layer dividing the intermetallic compound phase reach the two ends of the thickness direction of the intermetallic compound phase.

[0044] The oxide layer of the present invention is located on the outermost layer of the Zn-based alloy coating, and the separation of the intermetallic compound phase by the oxide layer is an essential component for satisfying the corrosion resistance and hydrogen release characteristics after coating.

[0045] First, the reasons for the improved corrosion resistance after coating due to the presence of the oxide layer of the present invention will be explained.

[0046] In steel plates with a typical Zn-based alloy coating that has not formed cracks ( Figure 1 When subjected to hot pressing, a relatively large unevenness with a height difference greater than 10 μm is formed on the surface of the Zn-based alloy coating. Figure 2 Regarding the reasons, the inventor speculates as follows.

[0047] When the temperature of the steel plate is increased by heating before hot pressing, an oxide layer forms on the surface of the Zn-based alloy coating. As a result, when the temperature of the steel plate exceeds the melting point of the Zn-based alloy coating, the coating between the oxide layer and the steel plate melts and forms a liquid. As heating continues and the temperature of the steel plate continues to rise, the oxide layer also continues to grow. At this point, in the direction perpendicular to the coating surface, the oxide layer grows by increasing its thickness; in the direction horizontal to the coating surface, the oxide layer grows by increasing its surface area while creating unevenness. This is because the coating between the oxide layer and the steel plate is a flowable liquid, thus allowing the oxide layer to change its shape.

[0048] When zirconium-based chemical conversion treatment and electrodeposition coating are applied to hot-pressed components with significantly uneven oxide layers, and the corrosion resistance after coating is evaluated, red rust formation becomes particularly noticeable, especially starting from the general sections that have never been cross-cut. The reasoning is that the electrodeposition coating does not follow the unevenness of the hot-pressed component surface; on the raised sections, the electrodeposition coating film is extremely thin, thus causing red rust to form in these areas.

[0049] In contrast, in steel plates with pre-formed cracked Zn-based alloy coatings, as in this invention (… Figure 3 When supplied for hot pressing, an oxide layer is formed in the portion where cracks existed before hot pressing. Figure 4 Therefore, even if the Zn-based alloy coating melts and forms a liquid due to heating before hot pressing, the oxide layer will separate the intermetallic compound phases, thus preventing significant unevenness in the overall Zn-based alloy coating. Therefore, from the perspective of the Zn-based alloy coating as a whole, a hot-pressed component with a flat Zn-based alloy coating can be obtained.

[0050] Therefore, when the hot-pressed component of the present invention is subjected to zirconium-based chemical conversion treatment and electrodeposition coating and the corrosion resistance after coating is evaluated, the film thickness of the electrodeposition coating is uniform. Therefore, in the general part where no cross-section is performed, local red rust will not occur, and excellent corrosion resistance after coating can be obtained.

[0051] It should be noted that, even without cracks forming in the Zn-based alloy coating on the steel plate, significant unevenness develops on the surface of the Zn-based alloy coating upon heating, and the oxide layer cannot keep up with its own deformation, sometimes resulting in peeling. The reactivity of the peeled oxide layer with the zirconium-based chemical conversion treatment solution is worse than that of the oxide layer present. Therefore, in the areas where the oxide layer has peeled, the coverage rate of the zirconium-based chemical conversion coating is reduced, and red rust sometimes forms in the uncoated areas. On the other hand, in the hot-pressed component of the present invention, the oxide layer is flat, and therefore, oxide layer peeling does not occur due to deformation during heating. Therefore, the zirconium-based chemical conversion coating can uniformly cover the entire surface of the hot-pressed component, preventing the aforementioned red rust caused by oxide layer peeling.

[0052] Furthermore, when no cracks form in the Zn-based alloy coating on the steel plate, the liquid Zn-based alloy coating can flow freely between the oxide layer and the steel plate when it melts due to heating. As a result, the diffusion of Zn from the Zn-based alloy coating into the steel plate becomes more active, and a thicker solid solution phase is formed. On the other hand, when cracks form in the Zn-based alloy coating on the steel plate, as in this invention, even if the Zn-based alloy coating melts due to heating, the liquid Zn-based alloy coating is restricted from movement by being surrounded by the oxide layer and remains in that position. As a result, the diffusion of Zn from the Zn-based alloy coating into the steel plate is suppressed, the formation of the solid solution phase is reduced, and the amount of residual intermetallic compound phase is increased. Compared with the solid solution phase, the intermetallic compound phase has a higher Zn content, thus further improving the corrosion resistance after coating.

[0053] For the reasons stated above, the presence of the oxide layer of the present invention significantly improves corrosion resistance after coating.

[0054] Next, the reasons for improving hydrogen release characteristics by manufacturing hot-pressed components using steel plates with cracks formed in the Zn-based alloy coating will be explained.

[0055] When steel sheets with Zn-based alloy coatings are used as hot-pressing steel sheets, hydrogen inevitably penetrates into the base steel sheet during the manufacturing process due to the intake of hydrogen generated in the electroplating solution and contact with water vapor in the atmosphere after electroplating.

[0056] In the absence of cracks in the Zn-based alloy coating on the steel sheet, hydrogen that has penetrated the steel sheet is released through the Zn-based alloy coating during the heating process before hot pressing. However, the hydrogen release pathway is not limited to the intermetallic compound phase, therefore, hydrogen release may not be efficient.

[0057] In contrast, when cracks form in the Zn-based alloy coating of the steel sheet, hydrogen is released via these cracks in addition to the aforementioned hydrogen release pathways, especially during the initial heating process. Therefore, hydrogen introduced during steel sheet manufacturing can be released efficiently. When there is no barrier layer (or coating) on ​​the steel sheet surface that hinders hydrogen release, or when heating is performed for a sufficiently long time (e.g., more than one hour), diffusible hydrogen in the steel sheet is generally considered to be released in a low-temperature range of 300–350°C. For this reason, the hydrogen release characteristics of steel sheets with cracks in the Zn-based alloy coating are improved in the low-temperature range.

[0058] On the other hand, it is known that during the heating process of hot pressing, in the high-temperature range above 400°C, water vapor in the furnace atmosphere reacts with the steel sheet or coating, and hydrogen is absorbed into the steel. To suppress hydrogen intrusion into the steel sheet in such a high-temperature range, forming an oxide-like barrier layer is effective. In hot-pressed steel sheets with cracks formed in Zn-based alloy coatings, in addition to the oxide layer formed laterally on the outermost surface, oxide layers are also formed corresponding to the cracked areas. Such oxide layers have the effect of thickening the oxide layer, which appears to act as a barrier layer against hydrogen intrusion. With the presence of such oxide layers, hydrogen intrusion in the high-temperature range is suppressed, resulting in hot-pressed components less prone to delayed fracture.

[0059] In the hot-pressed component of the present invention, the segmentation density per unit cross-section in at least one cross-section of the oxide layer is 10 segments / mm or more. When the segmentation density per unit cross-section in at least one cross-section of the oxide layer is less than 10 segments / mm, the aforementioned effect is not achieved, and the improvement in corrosion resistance and hydrogen release characteristics after coating is insufficient. From the viewpoint of improving corrosion resistance and hydrogen release characteristics after coating, the segmentation density per unit cross-section is preferably 50 segments / mm or more, and more preferably 100 segments / mm or more. The upper limit of the segmentation density per unit cross-section is not specifically specified. Excessive increase in the segmentation density per unit cross-section requires an increase in immersion time in acidic aqueous solution, which leads to a decrease in production efficiency and an increase in manufacturing costs. Therefore, the segmentation density per unit cross-section is preferably 300 segments / mm or less, and more preferably 200 segments / mm or less.

[0060] The aforementioned "at least one cross-section of the oxide layer" refers to at least one cross-section of the oxide layer in a direction perpendicular to the surface of the Zn-based alloy coating, which divides the total thickness of the intermetallic compound phase in the Zn-based alloy coating. It should be noted that the aforementioned segmentation density can be determined using the method described in the examples below.

[0061] In the hot-pressed component of the present invention, for the two orthogonal cross sections in the oxide layer, it is preferable that the segmentation density per unit cross section is 10 or more segmentation points / mm. As described above, the mechanism by which the presence of the oxide layer of the present invention improves the corrosion resistance and hydrogen release characteristics after coating is the unevenness suppression effect brought about by the plating segmentation, the peeling suppression effect of the oxide layer brought about by the reduction of unevenness, the effect of increasing the amount of intermetallic compound phase remaining due to the plating segmentation, and the effect of increasing the hydrogen release pathway, etc. For the oxide layer of the present invention, compared with only one cross section having a density of 10 or more segmentation points / mm, the effect of improving the corrosion resistance and hydrogen release characteristics after coating is greater when each of the two orthogonal cross sections has a density of 10 or more segmentation points / mm. Therefore, in the hot-pressed component of the present invention, for the two orthogonal cross sections in the oxide layer, it is preferable that the segmentation density per unit cross section is 10 or more segmentation points / mm. The above-mentioned segmentation density of the two cross sections is preferably 50 or more segmentation points / mm, more preferably 100 or more segmentation points / mm. For the same reasons as above, it is preferred to have 300 or less segments per mm, and more preferably 200 or less segments per mm.

[0062] The aforementioned "two orthogonal sections in the oxide layer" refer to two sections of the oxide layer perpendicular to the surface of the Zn-based alloy coating, dividing the total thickness of the intermetallic compound phase in the Zn-based alloy coating. These two sections are orthogonal to each other, located in the rolling direction (L direction) of the steel plate and perpendicular to the rolling direction (C direction). It should be noted that the division density of these two sections can be determined using the method described in the examples below.

[0063] 2) Steel plates for hot pressing

[0064] The hot-pressing steel sheet of the present invention has at least one component on at least one surface containing a total of 0.1 to 60% by mass of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhesion amount of 10 to 90 g / m. 2 The Zn-based alloy coating has cracks that divide it within the coating, and the crack density per unit cross-section in at least one cross-section of the Zn-based alloy coating is more than 10 segments / mm.

[0065] By including at least one element selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B in a total of 0.1 to 60% by mass in the Zn-based alloy coating, the melting point of the Zn-based alloy coating can be increased, resulting in hot-pressed components with excellent corrosion resistance after coating. When the total content of each element is less than 0.1% by mass, the melting point of the Zn-based alloy coating cannot be sufficiently increased, and sometimes the intermetallic compound phase disappears due to heating before hot pressing. As a result, hot-pressed components with the desired corrosion resistance after coating cannot be obtained. When the total content of each element exceeds 60% by mass, the dissolution reaction of Zn using acidic aqueous solutions is inhibited, thereby making crack formation difficult. Therefore, the corrosion resistance and hydrogen release characteristics of the hot-pressed component after coating become insufficient. The lower limit of the total content of the above-mentioned elements is preferably 0.2% by mass or more, and more preferably 4% by mass or more. The upper limit of the total content of the above-mentioned elements is preferably 55% by mass or less, more preferably 15% by mass or less.

[0066] Examples of Zn-based alloy coatings include electroplated Zn-Fe layers, hot-dip Zn layers, alloyed hot-dip Zn layers, hot-dip Zn-Al layers, and hot-dip Zn-Al-Mg layers.

[0067] In addition, by making the adhesion amount of the Zn-based alloy coating 10–90 g / m 2 This allows for the production of hot-pressed components with excellent corrosion resistance and hydrogen release characteristics after coating. The coating thickness is less than 10 g / m². 2 During hot pressing, the intermetallic compound phase disappears due to heating before the process, making it impossible to obtain hot-pressed components with the desired post-coating corrosion resistance. The coating thickness exceeds 90 g / m². 2 At this point, the effect of improving corrosion resistance after coating saturates, thus becoming uneconomical from a cost perspective. Furthermore, the hydrogen release characteristics may sometimes deteriorate. To further improve corrosion resistance after coating, it is preferable to set the adhesion amount to 30 g / m². 2 The above. The preferred adhesion amount is set to 80 g / m². 2 The following should be noted: the above-mentioned adhesion amount is the adhesion amount per single side.

[0068] In the hot-pressing steel plate of the present invention, there are cracks dividing the Zn-based alloy coating inside the Zn-based alloy coating, and the crack density per unit cross section in at least one cross section of the Zn-based alloy coating is 10 or more dividing parts / mm.

[0069] It should be noted that in the hot-pressing steel sheet of the present invention, the cracks dividing the Zn-based alloy coating refer to cracks formed in a direction perpendicular to the surface of the Zn-based alloy coating, i.e., from the surface of the Zn-based alloy coating toward the base steel sheet. Furthermore, from the viewpoint of corrosion resistance after coating, the crack width is set to 5 μm or less, more preferably 2 μm or less. There is no particular specification for the lower limit of the crack width. It is preferably set to 0.1 μm or more.

[0070] As detailed in section 1) above, in the hot-pressed component of the present invention, the oxide layer is located at the outermost layer of the Zn-based alloy coating, and the oxide layer divides the intermetallic compound phase, with a division density of 10 division points / mm or more per unit cross-section in at least one cross-section of the oxide layer. To obtain such a hot-pressed component, the hot-pressed steel sheet of the present invention has cracks dividing the Zn-based alloy coating within the Zn-based alloy coating, and the crack density per unit cross-section in at least one cross-section of the Zn-based alloy coating is set to 10 division points / mm or more. When the crack density per unit cross-section in at least one cross-section of the Zn-based alloy coating is less than 10 division points / mm, the improvement effect on the corrosion resistance and hydrogen release characteristics of the obtained hot-pressed component after coating is insufficient. From the viewpoint of improving corrosion resistance and hydrogen release characteristics after coating, a crack density of 50 division points / mm or more, and more preferably 100 division points / mm or more per unit cross-section, is preferred. Excessive increases in crack density per unit cross section require longer immersion time in acidic aqueous solutions, leading to decreased production efficiency and increased manufacturing costs. Therefore, the crack density per unit cross section is preferably 300 segments / mm or less, and more preferably 200 segments / mm or less.

[0071] In the hot-pressing steel sheet of the present invention, for the two orthogonal cross sections in the Zn-based alloy coating, the crack density per unit cross section is preferably 10 or more segments / mm. As explained in 1) above, for the oxide layer of the hot-pressing member of the present invention, compared with a density of 10 or more segments / mm in only one cross section, a density of 10 or more segments / mm in each of the two orthogonal cross sections is more effective in improving corrosion resistance and hydrogen release characteristics after coating. Therefore, in the hot-pressing steel sheet of the present invention, for the two orthogonal cross sections in the Zn-based alloy coating, the crack density per unit cross section is preferably 10 or more segments / mm. The crack density of the two cross sections is preferably 50 or more segments / mm, more preferably 100 or more segments / mm. For the same reasons as above, it is preferably 300 or less segments / mm, more preferably 200 or less segments / mm.

[0072] It should be noted that the cracks in this invention, as described in section 3) below, refer to cracks formed by performing a desired crack-forming process. Therefore, cracks generated during the preparation of test pieces for observing cross-sections are not included.

[0073] The Zn-based alloy coating of the present invention can be a single-layer Zn-based alloy coating, but within the scope of not affecting the effect of the present invention, a lower coating layer can be provided according to the purpose. For example, a Ni-based substrate coating can be used as the lower coating layer.

[0074] In this invention, in order to obtain a hot-pressed component with a pressure exceeding 1470 MPa after hot pressing, the base steel sheet used as the Zn-based alloy coating can, for example, contain, by mass percent, C: 0.20–0.35%, Si: 0.1–0.5%, Mn: 1.0–3.0%, P: 0.02% or less, S: 0.01% or less, Al: 0.1% or less, N: 0.01% or less, with the balance being Fe and unavoidable impurities. It should be noted that either cold-rolled or hot-rolled steel sheet can be used as the steel sheet. The reasons for the limitations of each component are described below.

[0075] C: 0.20–0.35%

[0076] Carbon (C) increases strength by forming martensite and other components that form the steel's microstructure. To achieve strengths exceeding 1470 MPa, a concentration of 0.20% or higher is required. However, concentrations exceeding 0.35% lead to a deterioration in the toughness of the spot weld. Therefore, the preferred C content is 0.20% to 0.35%.

[0077] Si: 0.1-0.5%

[0078] Si is an effective element for strengthening steel and obtaining good material properties. Therefore, a content of 0.1% or more is required. On the other hand, when it exceeds 0.5%, ferrite is stabilized, thus reducing hardenability. Therefore, the Si content is preferably set to 0.1% to 0.5%.

[0079] Mn: 1.0–3.0%

[0080] Mn is an effective element for increasing the strength of steel. To ensure mechanical properties and strength, it needs to contain more than 1.0%. On the other hand, when it exceeds 3.0%, surface enrichment during annealing increases, making it difficult to ensure coating adhesion. Therefore, the Mn content is preferably set between 1.0% and 3.0%.

[0081] P: below 0.02%

[0082] When the phosphorus (P) content exceeds 0.02%, grain boundary embrittlement occurs due to the segregation of P towards the austenite grain boundaries during casting, leading to a decrease in the balance between strength and ductility due to the deterioration of local ductility. Therefore, the P content is preferably set to 0.02% or less. It should be noted that there is no particular limitation on the lower limit of the P content. However, excessive reduction will lead to an increase in cost; therefore, the P content is preferably set to 0.001% or more.

[0083] S: below 0.01%

[0084] S forms inclusions such as MnS, leading to decreased impact resistance and cracking along the metal flow in the weld. Therefore, it is desirable to reduce the S content as much as possible, preferably to 0.01% or less. Furthermore, to ensure good elongated flange properties, it is more preferable to set it to 0.005% or less. It should be noted that there is no particular limitation on the lower limit of the S content. However, excessive reduction will lead to increased costs; therefore, the S content is preferably set to 0.0001% or more.

[0085] Al: below 0.1%

[0086] When the Al content exceeds 0.1%, the workability and hardenability of the raw steel sheet decrease. Therefore, the Al content is preferably set below 0.1%. It should be noted that there is no particular lower limit for the Al content. However, when the content is low, deoxidation during steelmaking is inhibited, and the uniformity and mechanical properties of the material decrease. Therefore, the Al content is preferably set above 0.001%.

[0087] N: less than 0.01%

[0088] When the nitrogen content exceeds 0.01%, AlN nitrides are formed during hot rolling and heating before hot pressing, reducing the punching workability and hardenability of the raw steel sheet. Therefore, the nitrogen content is preferably set to 0.01% or less. It should be noted that there is no particular limitation on the lower limit of the nitrogen content. However, excessive reduction will lead to increased costs; therefore, the nitrogen content is preferably set to 0.0001% or more.

[0089] In addition, in addition to the above-mentioned basic components, the present invention may also contain at least one component selected from Nb: less than 0.05%, Ti: less than 0.05%, B: 0.0002 to 0.005%, Cr: 0.1 to 0.3%, and Sb: 0.003 to 0.03% as needed to further improve the properties of the steel plate.

[0090] Nb: below 0.05%

[0091] Nitrogen (Nb) is an effective strengthening component for steel, but excessive amounts reduce its shape retention. Therefore, when Nb is present, the content is set to 0.05% or less. It should be noted that there is no particular lower limit to the Nb content. However, at low contents, the steel's strength-strengthening effect is not achieved; therefore, the Nb content is preferably set to 0.001% or more.

[0092] Ti: below 0.05%

[0093] Ti, like Nb, is effective in strengthening steel, but excessive amounts can reduce its shape retention. Therefore, when Ti is present, the content is set to 0.05% or less. It should be noted that there is no specific lower limit to the Ti content. However, low content will not provide sufficient strength enhancement; therefore, the Ti content is preferably set to 0.001% or more.

[0094] B: 0.0002~0.005%

[0095] Boron (B) has the effect of suppressing ferrite formation and growth from austenite grain boundaries, therefore, it is preferable to add 0.0002% or more. On the other hand, excessive addition of B significantly impairs formability. Therefore, in the case of B content, the content is set to 0.0002% to 0.005%.

[0096] Cr: 0.1–0.3%

[0097] Cr is useful for improving the strengthening and hardenability of steel. To achieve this effect, it is preferable to add 0.1% or more. On the other hand, alloys are expensive, so adding more than 0.3% results in a significant increase in cost. Therefore, in the case of Cr content, it is set at 0.1% to 0.3%.

[0098] Sb: 0.003~0.03%

[0099] Sb also has the effect of suppressing decarburization of the steel sheet surface during hot pressing. To achieve this effect, it needs to be added at least 0.003%. On the other hand, when the Sb content exceeds 0.03%, it leads to an increase in rolling load, thus reducing productivity. Therefore, in the case of Sb, it is set to 0.003% to 0.03%.

[0100] The balance other than those mentioned above consists of Fe and unavoidable impurities.

[0101] 3) Manufacturing method of steel plates for hot pressing

[0102] In this invention, a steel plate is formed by having at least one of the following on at least one surface: a component containing a total of 0.1 to 60% by mass of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhesion amount of 10 to 90 g / m. 2 By immersing the steel sheet with the Zn-based alloy coating in an acidic aqueous solution with a pH below 4.0 for more than 1.5 seconds, or by applying strain to the Zn-based alloy coating of the steel sheet, it is possible to manufacture hot-pressed steel sheets with the desired crack density.

[0103] Examples of Zn-based alloy coatings include electroplated Zn-Fe layers, hot-dip Zn layers, alloyed hot-dip Zn layers, hot-dip Zn-Al layers, and hot-dip Zn-Al-Mg layers.

[0104] When applying an electroplated Zn-Fe layer as a Zn-based alloy coating, a plating bath containing 200 g / L zinc sulfate heptahydrate, 240 g / L ferrous sulfate heptahydrate, pH 1.5, and a bath temperature of 50°C can be used, with a current density of 50 A / dm³. 2 Electroplating of Zn-Fe was carried out under the following conditions.

[0105] When applying a hot-dip Zn layer as a Zn-based alloy coating, a plating bath containing 0.2% Al and the balance consisting of Zn and unavoidable impurities at a temperature of 460°C can be used. The steel sheet is immersed in the plating bath for 2 seconds, thereby performing hot-dip Zn plating.

[0106] When applying an alloyed hot-dip Zn layer as a Zn-based alloy coating, a hot-dip Zn bath with a bath temperature of 460°C can be used. The steel sheet is immersed in the bath for 2 seconds and then alloyed for 15 seconds at an alloying temperature of 500°C, thereby performing alloyed hot-dip Zn coating.

[0107] When applying a hot-dip Zn-Al layer as a Zn-based alloy coating, a plating bath containing 5% Al and the balance being Zn and unavoidable impurities at a temperature of 500°C, or a plating bath containing 55% Al and the balance being Zn and unavoidable impurities at a temperature of 600°C, can be used. The steel sheet is immersed in the plating bath for 2 seconds to perform hot-dip Zn-Al plating.

[0108] When applying a hot-dip Zn-Al-Mg layer as a Zn-based alloy coating, a plating bath containing 4.5% Al, 0.5% Mg, and the balance consisting of Zn and unavoidable impurities at a temperature of 500°C can be used. The steel sheet is immersed in the plating bath for 2 seconds to perform hot-dip Zn-Al-Mg plating.

[0109] When the pH of the acidic aqueous solution exceeds 4.0, the etching ability decreases, thus reducing the crack formation effect and failing to achieve the desired crack density. Therefore, the pH of the acidic aqueous solution is set to 4.0 or lower. Preferably, the pH of the acidic aqueous solution is set to 2.0 or lower. To prevent excessive etching, the pH of the acidic aqueous solution is preferably set to 1.0 or higher. Furthermore, when the immersion time in the acidic aqueous solution is less than 1.5 seconds, etching will not proceed sufficiently, thus reducing the crack formation effect and failing to achieve the desired crack density. Therefore, the immersion time in the acidic aqueous solution is set to 1.5 seconds or higher. Preferably, the immersion time in the acidic aqueous solution is set to 2.0 seconds or higher. There is no specific upper limit to this immersion time, but from the viewpoint of preventing excessive etching, it is preferably set to 20 seconds or lower, more preferably 15 seconds or lower.

[0110] In particular, in this invention, by immersing the steel sheet in an acidic aqueous solution with a pH of 4.0 or lower for 1.5 seconds or more, it is possible to obtain a hot-pressing steel sheet in which the crack density per unit cross-section in the two orthogonal cross-sections of the Zn-based alloy coating is 10 or more crack segments / mm. In this invention, acidic aqueous solutions such as hydrochloric acid and sulfuric acid can be used.

[0111] In this invention, the acidic aqueous solution is preferably the plating solution used to form the Zn-based alloy coating. The plating solution used to form the Zn-based alloy coating is typically an acidic aqueous solution with a pH below 4.0. Therefore, when performing immersion treatment in this plating solution after forming the Zn-based alloy coating, a single liquid can be used for both the formation of the Zn-based alloy coating and the crack formation treatment, which is advantageous in terms of cost.

[0112] In this invention, the plating solution used to form the Zn-based alloy coating can be, for example, a plating solution containing 200 g / L zinc sulfate heptahydrate, 240 g / L ferrous sulfate heptahydrate, pH 1.5, and bath temperature of 50°C, which is used when applying an electroplated Zn-Fe layer.

[0113] Furthermore, in this invention, by inducing strain into the Zn-based alloy coating of the steel sheet, it is possible to manufacture hot-pressed steel sheets with a desired crack density. Examples of crack formation treatments that induce strain include uniaxial tension. Additionally, the strain is preferably 2% or more. From the viewpoint of preventing excessive increase in crack width, the strain is preferably set to 10% or less. The method of performing uniaxial tension is not particularly limited; examples include methods that induce strain by increasing the tension in the rolling direction in a specific section of the steel sheet manufacturing line after applying the Zn-based alloy coating.

[0114] 4) Manufacturing method of hot-pressed components

[0115] In this invention, a hot-pressed steel sheet manufactured by the method described in 3) above is heated to a temperature range of approximately 1000°C from the Ac3 phase transformation point and then hot-pressed, thereby obtaining a hot-pressed member with a desired segmentation density. Alternatively, the steel sheet may have at least one component on at least one surface containing a total of 0.1 to 60% by mass of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhesion amount of 10 to 90 g / m. 2 A steel plate (for hot pressing) with a Zn-based alloy coating, having cracks dividing the Zn-based alloy coating inside the Zn-based alloy coating, and having a crack density of 10 or more divisions per unit cross section in at least one cross section of the Zn-based alloy coating, is heated to a temperature range of Ac3 phase transformation point to 1000°C and then hot-pressed. Thus, a hot-pressed component with a desired division density can be obtained.

[0116] By setting the heating temperature of the hot-pressing steel sheet within the range of the Ac3 phase transition point to 1000°C, a Zn-based alloy coating having a solid solution phase, an intermetallic compound phase, and an oxide layer, as described in 1) above, can be obtained. When the heating temperature is below the Ac3 phase transition point, the required strength for a hot-pressed component may not be obtained; conversely, when the heating temperature exceeds 1000°C, the intermetallic compound phase in the Zn-based alloy coating may disappear. The heating temperature is preferably 800°C or higher, and preferably 950°C or lower. It should be noted that in this invention, the Ac3 phase transition point is determined using the thermodynamic calculation software Thermo-Calc.

[0117] Furthermore, there are no limitations on the holding time at the aforementioned heating temperature. It should be noted that, from the viewpoint of maximizing the retention of intermetallic compound phases to further improve corrosion resistance after coating, and from the viewpoint of avoiding hydrogen intrusion caused by water vapor introduced into the furnace during the holding time, the holding time is preferably set to within 3 minutes, more preferably within 1 minute, and even more preferably 0 minutes.

[0118] Furthermore, there are no limitations on the method of heating the steel plate for hot pressing. Examples include furnace heating using an electric furnace or gas furnace, electric heating, induction heating, high-frequency heating, and flame heating.

[0119] After heating, hot pressing is performed. During or immediately after the process, the material is cooled using a mold, water, or other cooling medium, thereby manufacturing the hot-pressed component. In this invention, the hot pressing conditions are not particularly limited, and stamping can be performed within a general hot pressing temperature range, i.e., 600–800°C.

[0120] Example 1

[0121] The present invention will now be specifically described based on embodiments. These embodiments are not intended to limit the invention, and appropriate modifications made within the scope of the spirit and intent are included within the scope of the invention.

[0122] As the base steel plate, a cold-rolled steel plate with a thickness of 1.4 mm (Ac3 phase transformation point = 730℃) is used, which contains, by mass %: C: 0.33%, Si: 0.25%, Mn: 1.9%, P: 0.005%, S: 0.001%, Al: 0.03%, N: 0.004%, Nb: 0.02%, Ti: 0.02%, B: 0.002%, Cr: 0.2%, Sb: 0.008%, with the balance consisting of Fe and unavoidable impurities.

[0123] The aforementioned base steel plate is subjected to electroplating of Zn, electroplating of Zn-Fe (Fe: 13%), hot-dip galvanizing of Zn (Al: 0.2%), alloyed hot-dip galvanizing of Zn (Fe: 10%), hot-dip galvanizing of Zn-Al (Al: 5%), hot-dip galvanizing of Zn-Al-Mg (Al: 4.5%, Mg: 0.5%), and hot-dip galvanizing of Zn-Al (Al: 55%), forming various Zn-based alloy coatings on the base steel plate.

[0124] For electroplating Zn-Fe (Fe: 13%), hot-dip Zn (Al: 0.2%), alloyed hot-dip Zn (Fe: 10%), hot-dip Zn-Al (Al: 5%), hot-dip Zn-Al-Mg (Al: 4.5%, Mg: 0.5%), and hot-dip Zn-Al (Al: 55%), the coatings are formed using the methods described. For electroplating Zn, a plating solution containing 440 g / L zinc sulfate heptahydrate, pH 1.5, and bath temperature of 50°C is used, with a current density of 50 A / dm³. 2 Electroplating is performed under specific conditions to form a coating.

[0125] The content and adhesion amount of each element in the obtained Zn-based alloy coatings are shown in Table 1. It should be noted that the elements in the Zn-based alloy coatings shown in Table 1 are elements other than the balance (Zn and unavoidable impurities).

[0126] The steel sheet thus obtained is processed by the following methods to induce cracks in the Zn-based alloy coating. The conditions for crack induction in each method are set as shown in Table 1.

[0127] A: Treatment of immersing the steel sheet in the plating solution composed of the above-mentioned bath.

[0128] B: Treatment of steel plates by immersion in hydrochloric acid

[0129] C: The treatment of uniaxial tension with a strain of 5% along the rolling direction of the steel plate should be noted. It should be noted that the coating is also subjected to a strain of 5% through the above treatment C.

[0130] For the Zn-based alloy coating on the obtained hot-pressed steel sheet, cross-sectional observation was performed to determine the crack density. Specifically, a scanning electron microscope (SEM) was used to observe the cross-section of the Zn-based alloy coating at 500x magnification, and the crack density per unit cross-sectional length was calculated (crack density per unit area / mm). To improve the accuracy of crack density determination, cross-sectional observations of one test material were performed from three fields of view, and the average value was taken as the crack density. It should be noted that the crack density was determined from two cross-sections: one along the rolling direction (L direction) and the other along a direction perpendicular to the rolling direction (C direction). The crack densities are shown in Table 1.

[0131] Next, the obtained hot-pressing steel plate is subjected to hot pressing. Specifically, a 150mm × 300mm test piece is cut from the obtained hot-pressing steel plate and heated in an electric furnace. The heat treatment conditions (heating temperature, holding time) are shown in Table 1. The heat-treated test piece is removed from the electric furnace and immediately hot-pressed using a cap-shaped die at a forming start temperature of 700°C, thereby obtaining a hot-pressed component. It should be noted that the shape of the obtained hot-pressed component is as follows: the flat portion of the upper surface has a length of 100mm, the flat portion of the side surface has a length of 50mm, and the flat portion of the lower surface has a length of 50mm. Furthermore, the bending radius R (radius of curvature) of the die is 7R for both shoulders of the upper surface and both shoulders of the lower surface.

[0132] For the obtained hot-pressed components, the phase structure of the coating is identified, the density of the oxide layer is measured, the corrosion resistance after coating is evaluated, and the hydrogen release characteristics are evaluated.

[0133] <Phase structure of the coating and segmentation density of the oxide layer>

[0134] For each coating layer of the obtained hot-pressed component, the phase structure (solid solution phase, intermetallic compound phase, oxide layer) was identified. Specifically, X-ray diffraction was used to determine the presence or absence of each phase in the solid solution phase, intermetallic compound phase, and oxide layer, and scanning electron microscopy (SEM) was used to confirm the location of each phase. If the location of the phase could be confirmed, it was recorded as "0 present" in the phase column of Table 1; if the location of the phase could not be confirmed, it was recorded as "× absent" in the phase column of Table 1.

[0135] In addition, test pieces for cross-sectional observation were cut from the flat portion of the upper surface of the obtained hot-pressed component, and the segmentation density of the oxide layer was determined by cross-sectional observation. Specifically, a scanning electron microscope (SEM) was used to observe the cross-section of the Zn-based alloy coating of the hot-pressed component at 500x magnification, and the segmentation density per unit cross-section (parts / mm) was calculated. To improve the accuracy of the oxide layer segmentation density measurement, three fields of view were observed on one test material, and the average value was taken as the segmentation density. It should be noted that the segmentation density was measured on two sections: one along the rolling direction (L direction) and the other perpendicular to the rolling direction (C direction). The results of the oxide layer segmentation density measurement are shown in Table 1.

[0136] <Corrosion resistance after coating>

[0137] To evaluate the corrosion resistance after coating, 70mm × 150mm test pieces were cut from the flat portion of the upper surface of the obtained hot-pressed component. These test pieces underwent zirconium-based chemical conversion treatment and electrodeposition coating. The zirconium-based chemical conversion treatment was performed under standard conditions using a PLM2100 manufactured by Pakase Sei Co., Ltd. (Japan). The electrodeposition coating was performed using a GT100V manufactured by Kansai Paint Co., Ltd., aiming for a coating film thickness of 10μm. Baking conditions were set at 170°C for 20 minutes. Subsequently, the hot-pressed component subjected to zirconium-based chemical conversion treatment and electrodeposition coating was subjected to a corrosion test (SAE-J2334) to evaluate the corrosion condition after 30 cycles.

[0138] For the transverse section, the maximum bulge width on one side from the transverse cut is measured, and the following criteria are used for judgment, with "◎" or "○" in the symbols shown below indicating acceptance. The evaluation results are shown in Table 2.

[0139] ◎: Maximum bulge width on one side < 1.5mm

[0140] ○: 1.5mm ≤ maximum bulge width on one side < 3.0mm

[0141] △: 3.0mm ≤ maximum bulge width on one side < 4.0mm

[0142] ×: 4.0mm ≤ Maximum bulge width on one side

[0143] For the general section that has not undergone cross-cutting, the following criteria shall be used for judgment, and the symbols “◎” or “○” shown below shall be considered as qualified. The evaluation results are shown in Table 2.

[0144] ◎: No red rust was produced in the general part.

[0145] ○: 1 location ≤ 3 locations where red rust has formed

[0146] △: 3 or fewer locations where red rust has formed < 10 locations

[0147] ×: 10 locations ≤ locations where red rust occurs

[0148] <Determination of Hydrogen Content in Hot-Pressed Components>

[0149] The hydrogen content in the obtained hot-pressed components was determined using gas chromatography. The heating rate for gas chromatography was set to 200°C / hour, and the final temperature was set to 300°C. Here, hydrogen content refers to the cumulative amount of hydrogen released from the steel within a temperature range from room temperature to 300°C, calculated by accumulating the hydrogen released at each temperature.

[0150] The following criteria will be used for evaluation, with "◎" or "○" in the symbols shown below considered as acceptable. The evaluation results are shown in Table 2.

[0151] ◎: Hydrogen content in hot-pressed components < 0.10 ppm

[0152] ○: Hydrogen content in hot-pressed components ≤ 0.10ppm < 0.15ppm

[0153] △: Hydrogen content in hot-pressed components ≤ 0.15ppm < 0.20ppm

[0154] ×: 0.20ppm ≤ Hydrogen content in hot-pressed components

[0155]

[0156] [Table 2]

[0157]

[0158] According to the results in Table 2, the hot-pressed components of the present invention exhibit excellent corrosion resistance after coating, particularly excellent corrosion resistance and hydrogen release characteristics after coating when subjected to zirconium-based chemical conversion treatment. Furthermore, if the hot-pressed steel sheet of the present invention is used, a hot-pressed component with excellent corrosion resistance and hydrogen release characteristics after coating can be obtained.

Claims

1. A hot-pressed component having a Zn-based alloy coating on at least one surface of a steel plate, the Zn-based alloy coating comprising: a solid solution phase containing Zn with the balance being Fe and unavoidable impurities; or a solid solution phase containing Zn and containing at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, B with the balance being Fe and unavoidable impurities; an intermetallic compound phase containing Fe with the balance being Zn and unavoidable impurities; or an intermetallic compound phase containing Fe and containing at least one selected from Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, B with the balance being Zn and unavoidable impurities; and a Zn-containing oxide layer. The oxide layer is located on the outermost layer of the Zn-based alloy coating, and the oxide layer separates the intermetallic compound phase. The oxide layer has a segmentation density of at least 10 segments per mm per unit cross section in at least one cross section.

2. The hot-pressed component according to claim 1, wherein, In the oxide layer, the orthogonal cross sections each have a segmentation density of more than 10 segments per mm.

3. A hot-pressing steel plate, wherein at least one surface of the steel plate contains at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, in an amount of 0.1 to 60% by mass, and the amount of the adhering material is 10 to 90 g / m². 2 Zn-based alloy coating, The Zn-based alloy coating contains cracks that divide it. The crack density per unit cross-section in at least one cross-section of the Zn-based alloy coating is more than 10 segments / mm. In the Zn-based alloy coating, in two orthogonal cross sections, the crack density per unit cross section is more than 10 segments / mm. The two orthogonal sections are the section along the rolling direction and the section perpendicular to the rolling direction.

4. A method for manufacturing a hot-pressing steel plate, comprising the method for manufacturing the hot-pressing steel plate as described in claim 3, wherein, The steel plate shall have at least one component on at least one surface containing a total of 0.1 to 60% by mass of at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhesion amount of 10 to 90 g / m. 2 The steel plate with the Zn-based alloy coating is immersed in an acidic aqueous solution with a pH below 4.0 for more than 1.5 seconds, or the Zn-based alloy coating is subjected to a strain of 2 to 10%.

5. The method for manufacturing a hot-pressing steel plate according to claim 4, wherein, The acidic aqueous solution is the plating solution used to form the Zn-based alloy coating.

6. A method for manufacturing a hot-pressed component, wherein, The hot-pressing steel plate obtained by the manufacturing method described in claim 4 or 5 is heated to a temperature range of Ac3 phase transformation point to 1000°C and then hot-pressed.

7. A method for manufacturing a hot-pressed component, wherein, The steel plate is heated to a temperature range of Ac3 phase transformation point to 1000℃ and then hot-pressed. The steel plate has on at least one surface an adhering material containing, in total, 0.1 to 60% by mass, at least one selected from Fe, Al, Mg, Si, Sr, Mn, Ti, Sn, In, Bi, Pb, and B, with the balance consisting of Zn and unavoidable impurities, and an adhering amount of 10 to 90 g / m. 2 The Zn-based alloy coating has cracks that divide the Zn-based alloy coating inside, and the crack density per unit cross-section in at least one cross-section of the Zn-based alloy coating is more than 10 divisions / mm.

Citation Information

Patent Citations

  • Plated steel sheet for hot press

    JP2003073774A

  • HIGH-STRENGTH Zn-Al-Mg-BASED SURFACE-COATED STEEL SHEET AND METHOD FOR PRODUCING SAME

    US20200173004A1